Impact of different FOPL systems (nutri-score vs. nutrinform) on consumer behaviour: Case study of the Slovak Republic - Radovan Savov; Filip Tkáč; Juraj Chebeň; Jana Kozáková; Jakub Berčík (Amfiteatru Economic Journal, 2022)
Undoubtedly, the proportion of the obese population has increased significantly in recent decades. Using FOPL (front-of-pack labelling) with clear nutritional information could also be helpful in eliminating this problem. The main aim of this contribution is to analyse the effects of using nutritional FOPL on consumers' choices. The analysis was based on the research, while 1000 respondents were asked to choose the desired product variant in three categories - cereals, yoghurts and protein bars without FOPL and with FOPL on their package. Two of the most discussed FOPL systems in the EU (Nutri-Score and Nutrinform) were analysed. Changes in consumer choice were analysed using non-parametric statistics, multiple correspondences, and correlation analysis. The results showed that both FOPLs affect the consumer in all products. The effects of FOPL resulted in choosing the best product (for cereals from 47% to 49%; for yoghurts from 28% to 31%; for bars from 28% to 42%) and improved consumers' choice. There are differences in effects between Nutri-Score (NS) and Nutrinform (NI). NS seems to be a more effective system because it has a stronger positive impact on consumers' choices. For cereals, the selection improved by 18% (NS) vs. 15% (NI), for yoghurts by 17% (NS) vs. 13% (NI), and for bars 28% (NS) vs. 20% (NI). The results among different product categories were not consistent. Consumers' attitudes toward a healthier diet can be improved using nutritional FOPL.
Keywords: I12; M31; M38; Q13; 330; food choice; Front-of-Pack labelling; health perception; healthy diet; Nutri-Score; Nutrinform; nutrition